PF-14 Gastric Leiomyoma in a Twelve Year Old Pulli dog – A Case Report - Osye Syahnita; Eva Zulfiati; Benda A Suwito; Sukmasari Arifah; Deni Noviana (Hemera Zoa, 2018)
Leiomyoma is a benign tumor arising from smooth muscle of hollow organs viz. uterus, vagina, intestines, stomach, urinary bladder and esophagus and is common in cow, dogs and fowl. Leiomyoma have slow-growing behaviour, localli invasive, malignant tumor of smooth muscle origin that typically is slow to metastasize4.